RECIPIENT OF THE 2005 IRVING K. ZOLA AWARD FOR EMERGING SCHOLARS IN DISABILITY STUDIES: 'It Is For The Mother': Feminists' Rhetorics of Disability During the American Eugenics Period - Lamp, Sharon (Disability Studies Quarterly, 2006)
Since the inception of the current U.S. disability rights movement, there has been tension between mainstream American feminists and disability rights activists over disabled women's right to control our bodies. While many nondisabled women now take such freedom for granted, disabled women continue to have decisions about our bodies determined by others who are part of the dominant culture. Why have mainstream feminists, who base their ideology upon the fallacy of a social construct of "inferiority," been unable to generalize their analysis to include disabled women? This essay contributes to women's and disability studies scholarship, exploring eugenic-period feminists' ideologies about disabled people to better understand the roots of the friction between these two movements. I compare the lives and work of two of the period's influential feminists: Charlotte Perkins-Gilman and Margaret Sanger, examining their use of eugenic language and ideology through close readings of papers, diaries and autobiographies in order to understand the formation of a movement to liberate non-disabled women at the expense of disabled people.